Research on Ethiopia’s health insurance and safety net programs results in more inclusive integrated programs for the poor - CGIAR Research Program on Policies, Institutions, and Markets (2017)
The Ethiopian Government and Development Agencies moved toward the development of more inclusive integrated programs around the Community Based Health Insurance (CBHI) and Productive Safety Net Program (PSNP) in Ethiopia as a result of research conducted under the Ethiopia Strategy Support Program that found that many PSNP beneficiaries were not enrolled in the CBHI, leaving their food security vulnerable to sudden illness, and despite their level of poverty, beneficiaries that were enrolled were not receiving a premium waiver.